White phosphorous civilian hand burns – An aid to timely treatment of a rare entity - Eimear Phoenix; Varit Suwanwalaikorn; Jordan Wilkinson; Colin M. Morrison; Roisin T. Dolan (Trauma Case Reports)
First discovered in 1669, white phosphorus is well known for its use in military warfare (Davis, 2002). Its application has since been expanded to include industrial disinfectants, fertilisers and fireworks (Davis, 2002). Exposure to white phosphorus can lead to severe chemical burns with high morbidity and potentially fatal systemic effects. Fortunately, civilian casualties from this potent agent are remarkably rare with few reports in the literature to date (Frank et al., 2008; Aviv et al., 2017). We present the case of a 27-year-old fisherman who sustained a chemical burn to his right hand from a substance suspected to be white phosphorus. We propose an evidence-based algorithm to guide non-military physicians literature on the acute management of white phosphorus burns to optimise timely emergency management of this uncommonly encountered substance.